Zigzag Dissociation Mode of 〈c + a〉 Dislocations on the 101¯1 Plane in Magnesium Alloys - Hao Sun; Zhigang Ding; Shuang Li; Xinping Zhang; Enrique J. Lavernia; Wei Liu (Advances in Materials Science and Engineering)
Fundamental understanding of the dissociation mode of 〈c + a〉 dislocations on the 101¯1 plane is required before the goal of improving the ductility of Mg alloys attained. In this study, our density-functional theory calculations reveal that the atoms in the 101¯1 plane slip along a zigzag trace through a low-energy pathway. We thus propose a novel zigzag dissociation mode based on this slip trace. In particular, the shuffling motion of atoms is observed at the position of stable stacking fault, which is closely related to the c/a ratio of the hexagonal closed-packed lattices.